Clinical value of Lp-PLA2, LDL-C, HDL-C, hs-CRP, leukocyte, FPG and HbA1c in type 2 diabetes mellitus patients with acute ischemic stroke - Shen, Huimin; Huang, Anyan; Wang, Bingxin; Huang, Xiaohua; Chen, Ruiqian (Frontiers in Endocrinology, 2025)
BackgroundTo evaluate the clinical significance of human plasma lipoprotein-associated phospholipase A2 (Lp-PLA2), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), high-sensitivity C-reactive protein (hs-CRP), leukocyte count, fasting plasma glucose (FPG), and glycated hemoglobin (HbA1c) in patients with Type 2 diabetes mellitus (T2DM) and acute ischemic stroke (AIS).MethodsA total of 155 T2DM patients with AIS, admitted to the Second Affiliated Hospital of Shantou University Medical College between October 2023 and October 2024, were included in the stroke group. Additionally, 86 T2DM subjects from the same period were included in the T2DM control group. Serum levels of Lp-PLA2, LDL-C, HDL-C, hs-CRP, leukocyte count, FPG, and HbA1c were compared between the T2DM-AIS group and the T2DM control group, as well as among T2DM-AIS patients with different infarct sizes and degrees of neurological impairment. The clinical value of the above indexes in the diagnosis of T2DM with AIS was analyzed by receiver operating characteristic curve (ROC curve).ResultsSerum levels of Lp-PLA2 (142.9 [115.8, 178.3] ng/L), LDL-C (3.4 [2.6, 4.2] mmol/L), hs-CRP (3.6 [1.5, 11.2] mg/L), leukocytes (8.0 [6.8, 10.3] × 10^9/L), FPG (10.2 [7.5, 14.4] mmol/L), and HbA1c (10.2 [7.5, 14.4] %) were significantly higher in the T2DM-AIS group compared to the T2DM control group (Lp-PLA2: 102.1 [76.6, 121.9] ng/L, LDL-C: 3.2 [2.4, 3.7] mmol/L, hs-CRP: 2.4 [0.9, 5.2] mg/L, leukocytes: 7.0 [6.1, 8.1] × 10^9/L, FPG: 7.4 [6.1, 10.3] mmol/L, HbA1c: 7.0 [6.4, 8.2] %). In contrast, serum HDL-C levels (1.1 [0.9, 1.3] mmol/L) were significantly lower than those in the control group (1.3 [1.1, 1.5] mmol/L), which correlated with larger infarct size and greater neurological injury. ROC curve analysis indicated that the combined use of seven tests had an AUC of 0.906, with a sensitivity of 77.40% and a specificity of 95.30%.ConclusionMonitoring serum levels of Lp-PLA2, LDL-C, HDL-C, hs-CRP, leukocyte count, FPG, and HbA1c provides a comprehensive assessment of cerebral infarction in T2DM patients with AIS and serves as auxiliary indicators for evaluating disease severity.